Pengembangan Sistem Aplikasi Portal Informasi Perguruan Tinggi di Indonesia Berbasis Website - Yudistira Sugandi; Bayu Priyambadha; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In choosing a college and course must be in accordance with their interests respectively because the interest is owned is the first step to achieve the desired learning outcomes, which is subsequently embodied in the selection of courses. But the fact is based on the survey that the authors do, there are 59% of students from 100 students who are confused and feel hesitant in determining which colleges or courses they should choose. One of the factors that caused it was the lack and the difficulty of the information they get about the higher education and study programs that exist in Indonesia. To overcome this, it is necessary an application information portal system of universities in Indonesia. This system will be made with web-based. This system will help students to facilitate in obtaining information about the college, as well as information about the study program. In addition, students can take the online exam and compare it with the passing grade of the study program that has been selected previously. This is done to determine the ability of the students whether it is sufficient or not to enter the college and the study program, and also with these results students can better prepare well. The system has been successfully tested using the white box testing method for unit testing with result low program complexity value means a high testability value, which means that the system is easily evaluated by testing and blackbox testing using validation where the result for validation testing for 71 functionality are 100% valid and the result of compatibility testing shows that the system can run on 3 typesof web browsers